BRICS on the African Energy Market: Current Situation and Prospects for Mutual Cooperation - Panina, Olga V.; Bakulina, Anna A.; Ploticyna, Lyubov A.; Krasyukova, Natalia L. (International Journal of Energy Economics and Policy, 2020)
The African energy market is one of the developing markets in search of foreign investments. The traditional investors, the EU and the USA, follow a policy inconsistent with the current situation – the emergence of new competitors, the BRICS countries. The purpose of the article is to assess the influence of the BRICS countries on the African energy market and to identify the extent of this influence. To this end, the authors have developed the presence index composed of the main indicators of the country’s participation in the African energy market. The results are then interpreted, in order to reveal the most effective strategy of the BRICS energy cooperation on African issues. The authors have identified the main specific features of the energy market in Africa and the main characteristics of the energy strategies proposed to African countries by the main players on the energy market (including the EU and the USA). This allows to develop a strategy for African countries regarding the development of their national markets. The main hypothesis of the article is that the African economies should diversify their portfolio of energy sector investments, but introducing only those strategies that contribute to the growth of their economy. Keywords: Africa, energy, BRICS, strategy, green energy, development JEL Classifications: O55, Q40 DOI: https://doi.org/10.32479/ijeep.9160